2012
DOI: 10.4103/1658-354x.93061
|View full text |Cite
|
Sign up to set email alerts
|

Suprascapular nerve block for the treatment of frozen shoulder

Abstract: Aims:The aim of our study was to compare the effects of suprascapular nerve block in patients with frozen shoulder and diabetes mellitus unresponsive to intraarticular steroid injections.Settings and Design:Ten patients without improvement of sign and symptoms after intraarticular injections were made a suprascapular nerve block.Methods:Pain levels and active range of movement of patients were recorded at initial attendance and after 1, 4, and 12 weeks. All patients’ simple pain scores, total pain scores, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 9 publications
(4 reference statements)
1
9
0
3
Order By: Relevance
“…Therefore, an IAI or SSNB may be beneficial before physical therapy. 6,27,37 An IAI, one of the most common procedures, can lead to satisfactory results in the treatment of adhesive capsulitis, with improved ROM and prompt pain reduction. 3,4,6,15,21,23,30 Previous studies have shown that an SSNB is also safe and effective, with faster and more efficient resolution of pain and restoration of ROM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an IAI or SSNB may be beneficial before physical therapy. 6,27,37 An IAI, one of the most common procedures, can lead to satisfactory results in the treatment of adhesive capsulitis, with improved ROM and prompt pain reduction. 3,4,6,15,21,23,30 Previous studies have shown that an SSNB is also safe and effective, with faster and more efficient resolution of pain and restoration of ROM.…”
mentioning
confidence: 99%
“…3,4,6,15,21,23,30 Previous studies have shown that an SSNB is also safe and effective, with faster and more efficient resolution of pain and restoration of ROM. 11,27,37…”
mentioning
confidence: 99%
“…[ 24 25 ] Suprascapular injection has shown to be effective in reducing shoulder pain and improving functional status for as long as 3 months, and ultrasound is the preferred mode of guidance. [ 26 27 ] Physical therapy is better tolerated after the procedure, and appropriate and regular physiotherapy can result in prolonged improvement in functional status and long-term reduction in pain; such an effect has especially been found in our experience in patients with adhesive capsulitis. In spite of the fact that there are other nerves that supply the shoulder capsule, suprascapular block-induced pain relief is profound.…”
Section: Introductionmentioning
confidence: 61%
“…administered SSNB under fluoroscopic guidance using a nerve stimulator needle in patients with frozen shoulder and diabetes mellitus unresponsive to intraarticular steroid injections. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] SSNB has been found to be effective in common conditions that result in chronic shoulder pain which include rotator cuff lesions, adhesive capsulitis (frozen shoulder), calcifying tendinitis, shoulder arthritis, rheumatoid arthritis, and stroke sequel. [ 5 6 7 8 9 ] The surface landmark technique of SSNB has undergone several modifications since it was first described by Wertheim and Rovenstien in 1941. [ 10 ] The most commonly used surface landmark technique of SSNB is the one described by Dangoisse et al .…”
Section: Introductionmentioning
confidence: 99%